What the CEO wants you to know : how your company really works - Ram Charan (Random house business books, 2017)
The classic on the universal laws of business success, completely revised and updated for today's leaders. Completely rewritten for today's business world, What the CEO Wants You to Know, expanded and updated, describes the fundamentals behind every business, from street vendors in Mumbai, to Fortune 500 companies. Drawing on stories from Uber, Amazon, Apple, Toyota, Netflix, Lyft, The Limited, Walmart, GE and Starbucks, Charan, in the most accessible language imaginable, explains the ins and outs of how companies work, from gross revenue and operating costs, to inventory and cash flow, from turnover, profits and margins, to return on capital and accounts payable and receivable, from product quality to sales.